2007
DOI: 10.1007/s10336-007-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of repeated handling and bleeding in wild caught Great Tits Parus major

Abstract: Handling and bleeding are frequently used procedures in avian research and several studies show that they can exert short-term effects, such as elevation in corticosterone levels. However, the long-term effects of exposure to such manipulations are largely unknown, but could have important implications, especially for much of the long-term research on birds and experiments that involve longitudinal assessments. In this study, we evaluated the effect of handling and bleeding on some physiological and behavioura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
2
12
2
Order By: Relevance
“…Although the respiratory frequency is often used to measure the stress (Carere and van Oers 2004, van Oers and Carere 2007, Torné-Noguera et al 2014), no effect was observed in the present study. The behaviour of the chicks was scored, and their physiological stress was estimated thus allowing to assess the difference in behavioural and physiological responses of naïve individuals between the two experimental groups.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Although the respiratory frequency is often used to measure the stress (Carere and van Oers 2004, van Oers and Carere 2007, Torné-Noguera et al 2014), no effect was observed in the present study. The behaviour of the chicks was scored, and their physiological stress was estimated thus allowing to assess the difference in behavioural and physiological responses of naïve individuals between the two experimental groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, most of the time, the impact of investigators is seen from the disturbance effect point of view either on breeding success (Bolduc and Guillemette 2003, Blackmer et al 2004, Ibáñez-Álamo et al 2012, growth of chicks (Sandvik and Barrett 2001, O'Dwyer et al 2006, Carey 2009, 2011, or on behaviour and physiology (van Oers and Carere 2007) but rarely, to our knowledge, considering the identity of the people in charge of the experiment on wildlife fauna (see, however, Slobodchikoff et al 1991, Levey et al 2009, Marzluff et al 2010, Lee et al 2011, Davidson et al 2015. Indeed, most of the time, the impact of investigators is seen from the disturbance effect point of view either on breeding success (Bolduc and Guillemette 2003, Blackmer et al 2004, Ibáñez-Álamo et al 2012, growth of chicks (Sandvik and Barrett 2001, O'Dwyer et al 2006, Carey 2009, 2011, or on behaviour and physiology (van Oers and Carere 2007) but rarely, to our knowledge, considering the identity of the people in charge of the experiment on wildlife fauna (see, however, Slobodchikoff et al 1991, Levey et al 2009, Marzluff et al 2010, Lee et al 2011, Davidson et al 2015.…”
Section: Methodological Caveatsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had reason to expect a physiological impact of predator image exposure because long-term effects of stressful events, such as capture [84], nest predation [27], translocation [85], restraint [86] or high stocking density [30], on different behavioural and physiological parameters have been recorded in birds. Furthermore, we detected that exposure to a predator image reduced total locomotor activity in greenfinches for at least 44 h after the treatment [87].…”
Section: Discussionmentioning
confidence: 99%